Internalisasi Pendidikan Karakter Dalam Kurikulum Pendidikan Agama Islam Di Min 1 Lebong - Nurhayani Nurhayani; Deri Wanto (LPPM IAIN Sorong, 2023)
Abstract: Moral degradation has occurred and has become a serious threat to world civilization, so it is a challenge that Islamic religious education must be able to solve. One of the efforts being made is strengthening and internalizing character education in the Islamic education curriculum. Character education is an inseparable part of the implementation of Islamic religious education. Thus character education can be internalized in the PAI curriculum and learning. This study aims to determine the efforts made by MIN 1 Lebong to improve the morals of the nation's children by internalizing character education in the PAI curriculum. This study uses a qualitative method with a field research approach. The result of the research is the design of the RPP design that includes the values ​​of the nation's character and in the process always instills character education values ​​such as religious, honest, tolerance, discipline, hard work, creative, independent, democratic, curiosity, enthusiasm. nationality, love for the homeland, appreciate achievements, friendly/communicative, love peace, love to read, care for the environment, care about social and responsibility. Apart from intra-curricular activities, character education is also applied to co-curricular and extra-curricular activities such as tahsin, khatil and muhadharah as well as PHBI, activities tahfizh and scouts.